The Serum Level of Fibroblast Growth Factor-23 and Calcium-Phosphate Homeostasis in Obese Perimenopausal Women - M. Holecki; J. Chudek; A. Więcek; M. Titz-Bober; J. Duława (International Journal of Endocrinology)
Plasma FGF-23 concentrations and its relationship with calcium-phosphate homeostasis were evaluated in 48 perimenopausal obese women and in 29 nonobese controls. Serum parathyroid hormone, 25-hydroxyvitamin D3, CTX1, osteocalcin, total calcium, phosphorus, creatinine, and plasma intact FGF-23 concentrations were assessed. DXA of lumbar spine and femoral neck was performed to determine bone mineral density (BMD). Plasma iFGF-23 concentration was significantly higher in obese patients (by 42%) and correlated with age and BMD of proximal femur (R=-0.346; R=0.285, resp.) but not with markers of bone turnover. However, serum phosphorus level in obese subjects was significantly lower. iFGF-23 concentration correlated significantly with body mass index (R=0.292) and fat content (R=0.259) in all study subjects. Moreover, a significant correlation between iFGF-23 and iPTH (R=0.254) was found. No correlation between serum phosphorus or eGFR and plasma iFGF-23 and between eGFR and serum phosphorus was found. Elevated serum iFGF-23 concentration may partially explain lower phosphorus levels in the obese and seems not to reflect bone turnover.